Kontroversi Teori Nasakh Wal Mansukh Menurut Para Ulama: Studi atas Pemikiran Abdullah Ahmad An-Naim - Arman, Arman (STAI Darul Kamal NW Kembang Kerang, 2023)
Nasakh theory to this day is still being debated in the understanding of scholars, a very complex issue in this theory is that there are scholars who reject the theory of Nasakh wal Mansukh, on the grounds that there is no annulment or abolition of syar'i law contained in the Qur'an. an, the theory of Nasakh is permissible according to reason, but according to Shari'a, nasakh may not occur in the Qur'an. The purpose of this study is to explain and review the theory of nasakh wal mansukh by presenting some of the views of classical and contemporary scholars, then the author presents the opinions of contemporary scholars, namely Abdullah Ahmad An-Naim. This research is a type of research that uses qualitative methods and is descriptive analysis in nature, namely by systematically describing and describing discussion materials obtained from various sources and then analyzed to obtain research results. The results of this study turned out that behind the controversy of the theory of Nasakh wal Mansukh among scholars, both scholars who agreed with the theory of texts and those who disagreed emphasized that from the two groups of scholars above in providing the basis for rejecting or accepting the theory, it turned out that the basis or verse they use the same Q.S. Al-Baqarah:106 in providing a basis for their argument, but they only differ in interpretive positions. Because this research focuses on the theory of texts offered by Abdullah Ahmad An-Naim, the author will explain his views, An-Naim in defining texts is defined as having been deleted, while the words munsi'ha are defined as 'postponing' their implementation or application, from the definition given the author has explained that An-Na'im does not acknowledge the existence of deletions in the text of the Qur'an, in his opinion that there is only a delay in its implementation until the circumstances and conditions are right for enacting the text.